2007
DOI: 10.1370/afm.755
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Participatory Research by Family Physicians

Abstract: In the past, researchers have inadvertently caused stigmatization of various populations, fi rst by not involving community members and then through publishing negative fi ndings. In contrast, participatory research, which is based on a partnership between researchers and those affected by the issue being studied, promotes the voice of those being researched. This essay highlights key principles, processes, complexities, and challenges of participatory research and outlines when participatory research is not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Some authors advocate that essential components of community involvement in research are shared decision making, developing appropriate research priorities, cultural competence, and building and maintaining trust between the community and researchers. 7,12,13,[15][16][17][18] To implement these components in a sustainable fashion, the infrastructure barriers that come from the piecemeal or study-specific funding of most PBRNs need to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate that essential components of community involvement in research are shared decision making, developing appropriate research priorities, cultural competence, and building and maintaining trust between the community and researchers. 7,12,13,[15][16][17][18] To implement these components in a sustainable fashion, the infrastructure barriers that come from the piecemeal or study-specific funding of most PBRNs need to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an extensive review of the literature, Israel et al (2005Israel et al ( , 2008 and Macaulay (2007) have identified a list of nine principles or characteristics of CBPR that CPPR acknowledges. These characteristics include: (1) recognising community as a unit of identity; (2) facilitating a collaborative, equitable partnership in all phases of the research, involving an empowering and powersharing process that attends to social inequities; (3) building upon strengths and resources within the community; (4) integrating and achieving balance between knowledge generation and intervention for mutual benefit of all partners; (5) fostering co-learning and capacity-building among all partners; (6) focusing on local relevance of public health problems and ecologic perspectives that recognise and attend to the multiple determinants of health; (7) disseminating results to all partners and involving them in the dissemination; (8) involving systems development using a cyclical and iterative process; and (9) involving a long-term process and commitment to sustainability.…”
mentioning
confidence: 99%
“…Like participatory research approaches, where research is conducted through active research-community partnerships (Macaulay, 2007;Williams, Shelley, & Sussman, 2009), integrated KT involves stakeholders at key junctures throughout the knowledge-to-action cycle. McGrath and colleagues (2009) identify areas for joint decision-making that include shaping research questions, methods, data collection, and tools development; interpreting study findings; and crafting and disseminating messages.…”
mentioning
confidence: 99%
“…An IKT approach, similar to participatory research approaches, has many potential advantages: knowledge users bring different knowledge, skills, and insights to research; users have a unique understanding of results; and users are well positioned to move results into practice (they have expertise within their communities and a network of contacts). In addition, an IKT approach improves the relevance and use of the research to inform policy/practice change (Flicker, Savan, Kolenda, & Mildenberger, 2008;Macaulay, 2007;Williams et al, 2009). Knowledge users understand the community context and act as champions to link and share results (CIHR, 2009).…”
mentioning
confidence: 99%